The Oxidative Damage and Inflammation Mechanisms in GERD-Induced Barrett’s Esophagus - Han, Deqiang; Zhang, Chao (Frontiers in Cell and Developmental Biology, 2022)
Barrett's esophagus is a major complication of gastro-esophageal reflux disease and an important precursor lesion for the development of Barrett’s metaplasia and esophageal adenocarcinoma. However, the cellular and molecular mechanisms of Barrett’s metaplasia remain unclear. Inflammation-associated oxidative DNA damage in Barrett’s esophagus could contribute to DNA damage and gene instability, but its involvement in the occurrence of Barrett's esophagus has not been reported. It has been demonstrated that Poly ADP-ribose polymerases (PARPs)-associated ADP-ribosylation plays important role in DNA damage and inflammatory response. Previous study indicated that there is inflammatory infiltration and oxidative DNA damage in the lower esophagus due to acid/bile reflux, and gastric acid could induce DNA damage in culture esophageal cells. This review will discuss about the mechanisms of Barrett’s metaplasia and adenocarcinoma underlying oxidative DNA damage in gastro-esophageal reflux disease patients based on recent clinical and basic findings.